2020
DOI: 10.1002/mame.202000440
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evolution of Polyamide 6 (PA6)‐Based Thermoplastic Elastomers during Heating and Cooling Investigated by Moving‐Window 2D Correlation Infrared Spectroscopy

Abstract: To illustrate the complex phase evolution of polyamide 6 (PA6)‐based thermoplastic elastomer (TPAE‐50) with a three‐phase system (a pure PA6 crystalline phase, a phase‐separated mesophase, and a mixed phase) during cooling and heating, the in situ IR spectroscopy combined with moving‐window 2D correlation analysis is employed. The mixing of PA6 amorphous domains with soft domains and the melting of imperfect PA6 crystalline domains of TPAE‐50 occur from 60 °C with the increasing temperature. Brill transition h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In addition, the peaks at 3290–3300 cm –1 in TPAE and its chain-extended blends correspond to the N–H stretching vibrations, while the sharp peaks at 1638 and 1543 cm –1 separately correspond to the C=O stretching vibrations (amide I) and CO–N–H bending vibration (amide II) induced. 22 24 It can be observed that the N–H stretching vibration intensity and the peak area decreases, while the C=O stretching vibration (amide I) and CO–N–H bending vibration (amide II) intensity and peak area increase in the modified TPAE compared with raw material, which further illustrates that anhydride groups in SMA can react with amino groups in TPAE.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, the peaks at 3290–3300 cm –1 in TPAE and its chain-extended blends correspond to the N–H stretching vibrations, while the sharp peaks at 1638 and 1543 cm –1 separately correspond to the C=O stretching vibrations (amide I) and CO–N–H bending vibration (amide II) induced. 22 24 It can be observed that the N–H stretching vibration intensity and the peak area decreases, while the C=O stretching vibration (amide I) and CO–N–H bending vibration (amide II) intensity and peak area increase in the modified TPAE compared with raw material, which further illustrates that anhydride groups in SMA can react with amino groups in TPAE.…”
Section: Resultsmentioning
confidence: 90%
“…The structures and properties of TPAEs are predominantly dependent on their intrinsic segment compositions, especially the relative content and chain length of the components. [ 58,59 ] Meanwhile, they are also significantly hinged on the variation of processing conditions [ 60 ] as well as different use environments such as temperature [ 27,61 ] and exterior force. [ 62,63 ] For these reasons, the correlations between structures and properties under the action of different conditions mentioned above were extensively studied since the advent of TPAEs.…”
Section: Structures and Propertiesmentioning
confidence: 99%
“…In recent years, the Yuan group [ 73 ] also employed a similar technique to elucidate the phase evolution of PA6‐based TPAEs prepared in the work [ 26 ] during heating and cooling processes. A morphological model of the TPAEs at room temperature was proposed to conveniently describe the morphological changes of the TPAEs under varying temperatures.…”
Section: Structures and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that T B is highly dependent on the crystallization conditions, which affects the characteristics such as the thickness distribution of lamellae and the H-bond organization . In addition, blending with fillers ,,, and chemical modification by inserting the comonomers , in the main chain are two effective ways to control T B . Liu et al found that the T B of PA66 was decreased by blending with silicate and attributed it to the strong interaction between PA66 chains and surfaces of silicate layers .…”
Section: Introductionmentioning
confidence: 99%